Peningkatan Keselamatan di Rumah Sakit melalui APAR dengan Teknologi (Literatur Review) - Silviana Ramadina; Mursyidul Ibad (Yayasan Literasi Sains Indonesia, 2024)
Improving safety in hospitals is a crucial aspect in efforts to provide quality health services. This article is a literature review that discusses the important role of Light Fire Extinguishers (APAR) supported by technology in increasing the level of safety in hospitals. This review explores a number of studies that reveal the benefits of using fire extinguishers equipped with advanced technology, such as fire sensors, automatic monitoring and rapid notification, in reducing the risk of fire in hospital environments. Apart from that, this article also reviews regulatory aspects, personnel training, and other factors that are key to the successful implementation of APAR technology in the hospital context. The writing method used is descriptive qualitative with a literature review approach where the data comes from various online sources, such as Google Scholar. The results of this literature review provide a better understanding of how the use of APAR integrated with technology can be an effective solution to improve the safety of patients, medical staff and facilities in hospitals.